Genome-wide survey and genetic characteristics of Ophichthus evermanni based on Illumina sequencing platform. Issue 5 (27th May 2022) - Yang, Tianyan; Ning, Zijun; Liu, Yuping; Zhang, Shufei; Gao, Tianxiang
Abstract: Ophichthidae fishes limit to continental shelf of all tropical and subtropical oceans and contain more than 350 species, representing the greatest specialization diversity in the order Anguiliformes. In the present study, we conducted a genome survey sequencing (GSS) analysis of Ophichthus evermanni by Illumina sequencing platform to briefly reveal its genomic characteristics and phylogenetic relationship. The first de novo assembled 1.97 Gb draft genome of O. evermanni was predicted based on K-mer analysis without obvious nucleotide bias. The heterozygosity ratio was 0.70%, and the sequence repeat ratio was calculated to be 43.30%. A total of 9016 putative coding genes were successfully predicted, in which 3587 unigenes were identified by gene ontology (GO) analysis and 4375 unigenes were classified into cluster of orthologous groups for enkaryotic complete genomes (KOG) functional categories. About 2, 812, 813 microsatellite motifs including mono-, di-, tri-, tetra-, penta- and hexanucleotide motifs were identified, with an occurrence frequency of 23.32%. The most abundant type was dinucleotide repeat motifs, accounting for 49.19% of the total repeat types. The mitochondrial genome, as a byproduct of GSS, was assembled to investigate the evolutionary relationships between O. evermanni and its relatives. Bayesian inference (BI) phylogenetic tree inferring from concatenated 12 protein-coding genes (PCGs) showed complicated relationships among Ophichthidae species, indicating a polyphyletic origin of the family. The results would achieve more thorough genetic information of snake eels and provide a theoretical basis and reference for further genome-wide analysis of O. evermanni.